Study on control strategy and application of a new harmonic detection method in three‐phase four‐wire APF. (3rd October 2018) - Li, Delu
Summary: In the three‐phase four‐wire low‐voltage distribution network, a large number of nonlinear loads are put into use, which makes the harmonic and three‐phase imbalance problems of a three‐phase four‐wire system more and more prominent. In addition, it seriously affects the energy quality of the power network. The three‐phase four‐wire active power filter (APF) is one of the effective measures to solve these problems. In this paper, a new harmonic detection method for the three‐phase four‐wire APF is proposed, and it is applied to the control strategy of three‐phase four‐wire APF. Then, the advantages and disadvantages of various detection algorithms of harmonic current in a three‐phase four‐wire system are summarized. The digital phase‐locked technology based on a generalized integrator is studied, and the method of extracting the positive‐sequence component of fundamental wave voltage by using the frequency‐selecting characteristic of a generalized integrator is put forward. The generalized integrator and the ip‐iq method are combined to realize the detection of any order harmonics. A novel method of extracting fundamental wave components from three‐phase four‐wire APF harmonics using the ensemble empirical mode decomposition (EEMD) algorithm is put forward, and the function of upper and lower envelopes is optimized by using a cubic spline fitting curve in the process of EEMD. In order to reduce the operation time of the EEMD algorithm and improve the efficiency and real‐time function of harmonic detection, the cubic spline fitting curve is used to obtain the function of upper and lower envelopes in the process of decomposition.